Hacia el desarrollo de alternativas sostenibles al combustible diésel: síntesis de 1,1-dimetoximetano (OME1) a través de catálisis bifuncional - Herrera, Jose Efrain (2023)
The environmental impact generated by the extensive utilization of fossil-based fuels has driven the need to develop renewable energy sources, as well as sustainable processes for liquid fuels production. Oxymethylene ethers (OMEs) are oxygenated compounds that have emerged as a potential alternative to replace Diesel fuel, helping to reduce the formation of soot and nitrogen oxides (NOx) during its combustion. Among this family of compounds, 1,1-dimethoxymethane (OME1) has special interest because of its versatility as an industrial solvent or as a chemical intermediate. Specifically, it can be used as a feedstock to produce higher chain OMEs. The direct synthesis of OME1 involves the selective oxidation of methanol over bifunctional catalysts, which have been widely studied during the last decades. This work summarizes the main features of the different catalytic systems developed, which play a fundamental role for the commercial production of 1,1-dimethoxymethane